2016
DOI: 10.1519/jsc.0000000000001091
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Strength and Interval Endurance Training in Elite Water Polo Players

Abstract: This study compared the effects of different high-intensity interval training (HIIT) intervals performed concurrently with strength and specific water polo training on performance indices of elite players. During the precompetition season, 2 water polo clubs were assigned to either HIIT of 4 × 4 minutes (n = 7, HIIT4 × 4) or HIIT of 16 × 100-m swimming efforts (n = 7, HIIT16 × 100). Both clubs applied the swimming (6% above the speed corresponding to blood lactate concentration of 4.0 mmol · L) and strength tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Indeed, we observed that the aerobic and anaerobic potential of IL players was higher by 8–10% compared to the NL players. Interestingly, the V4 values presently observed are similar to those observed in a previous study (1.29–1.35 m·s −1 ) [4] regarding top-class water polo players and are also comparable to those reported by Fernandes et al [16] concerning long-distance swimmers. Nevertheless, no difference was found for lactate tolerance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, we observed that the aerobic and anaerobic potential of IL players was higher by 8–10% compared to the NL players. Interestingly, the V4 values presently observed are similar to those observed in a previous study (1.29–1.35 m·s −1 ) [4] regarding top-class water polo players and are also comparable to those reported by Fernandes et al [16] concerning long-distance swimmers. Nevertheless, no difference was found for lactate tolerance.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the high presence of dynamic actions that occur in water polo match-play (body contacts/wrestling, fast swimming, offence or defence actions), an adequate strength level is essential for water polo players [3]. Accordingly, dry-land strength training has been extensively recommended in the literature, as it induces considerable gains in the maximal strength level of elite or top-class water polo players [4,12,13]. Previous studies in land-based team-sports have found higher values of absolute maximal strength in international-level athletes compared to national-level athletes [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several sports, CT is a usual method of training, as it combines the specific motions of sports, such as swimming or running, with resistance training to obtain gains in several actions/tasks crucial for increase sport performance [48][49][50][51]. Our search revealed that among the studies on CT intensity, only a few reported data on professional athletes [37,42,44].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic endurance is one of the most basic body ability of sports fitness, and it can ensure the athletes' body under the condition of high strength, high against movement quality and also it is the ability to work for a long time [1].Aerobic endurance training is also an integral part of football player physical ability training.The essential characteristics of modern football match determines the soccer movement the special physical ability must be combined with a very, not with tactical purpose physical performance characteristics with football "special" run counter to the nature of the physical features [2].…”
Section: Introductionmentioning
confidence: 99%